Dekonstruksi Mitos Keagamaan dalam Perspektif Semiotika Roland Barthes: Analisis Wacana Keislaman Kontemporer di Indonesia - Meliza; Fadhila Rahmi; Abdul Matin Bin Salmand (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study analyzes the construction of religious myths in contemporary Islamic discourse in Indonesia through Roland Barthes’ semiotic perspective. It focuses on the hijab symbol, the concept of sabr, the labeling of kafir, and exclusive salvation claims as forms of meaning naturalization in digital public spaces. The study employs a descriptive-critical qualitative approach using semiotic discourse analysis. Data were collected from digital religious texts and analyzed through sign identification, denotative and connotative analysis, and myth deconstruction. The findings reveal that religious symbols have undergone mythologization processes that make them appear as natural truths. The hijab is constructed as a singular symbol of piety, sabr as legitimation of resignation, kafir as a producer of identity boundaries, and exclusive salvation claims as reinforcement of group superiority. This study confirms that religious meaning is shaped by power relations and discursive reproduction. The findings contribute to interdisciplinary Islamic studies through integrating semiotics, Qur’anic interpretation, sociology of religion, symbolic anthropology, and discourse criticism.